Developing and Approving a LETS! Teach, Affirm, Learn, Know (LETS! T.A.L.K.) Curriculum for Grades K-2 in a Public-School System. Issue 3 (3rd July 2021) - Weil, Mira; Apala Flaherty, Aneliese; Gubrium, Aline
Abstract: Few public schools in Massachusetts offer a sex-positive, inclusive sexuality education curriculum at the elementary school level. One Massachusetts public elementary school identified the need for such a program that addresses communication, sexuality, gender, and consent. The LETS! Teach, Affirm, Learn, Know (T.A.L.K.) curriculum was developed, literally from the "bottom up, " with initial development and program approval focused on the kindergarten through second grades, through a town-gown collaboration between a university and its local public school district in 2018–2019. In this article, we describe the LETS! T.A.L.K. curriculum development and approval process, and present key research findings from our community-based process.